Influenza vaccination in Austria: Persistent resistance and ignorance to influenza prevention and control - Kunze, Ursula; Böhm, Gabriela; Prager, Bernhard; Groman, Ernest (Central European journal of public health, 2019)
OBJECTIVE: In the Austrian population approximately 350,000-400,000 cases and 1,000-1,200 deaths are observed during an average epidemic, which puts influenza-related deaths on top of the list of vaccine-preventable cases of death. In face of extensive vaccination recommendations, the current vaccination rate of the general population of about 6% is one of the lowest worldwide. The objective of this study was to provide an update regarding the use of influenza vaccination in Austria over the period 1982-2015. METHODS: This paper presents data on influenza vaccine use in Austria displayed by the number of distributed doses per 1,000 population over a period of 33 years. Further data was collected from representative population-based telephone surveys. RESULTS: Austria has always been among the countries with a low number of distributed doses of influenza vaccine. The highest number ever was reached in 2006 with 142 doses/1,000. From 2007 onwards, a steady decrease happened to 62 doses/1,000 in the 2015/16 season, which corresponds to the level of the mid-nineties. CONCLUSION: Despite the fact that Austria is a country with comprehensive recommendations for influenza vaccination, this vaccination continues to be misjudged by the Austrian population and many areas of the medical system. From a public health point of view, this situation is not acceptable. Efforts must be increased to attain a much higher vaccination rate, e.g. the importance of the healthcare workers' influence must be recognized, the options of social marketing have to be utilized and studies on the main barriers in Austria are urgently needed.
Keywords: zdravotnický personál; pacientův souhlas se zdravotní péčí; Austria; vakcíny proti chřipce; Influenza, Human; zdravotní politika; Vaccination; vakcinace; Influenza Vaccines; influenza; Health Personnel; Health Knowledge, Attitudes, Practice; Humans; dose distribution; vaccine use; Health Policy; zdraví - znalosti, postoje, praxe; chřipka lidská; Patient Acceptance of Health Care; Rakousko; lidé; vaccination